Jo van Gogh-Bonger the woman who made Vincent famous - Luijten, Hans 1961- (Bloomsbury Visual Arts, 2023)
"Little known but no less influential, Jo van Gogh-Bonger (1862–1925) was the wife of Theo and sister-in-law of Vincent van Gogh. When the brothers died soon after each other, she took charge of van Gogh’s artistic legacy in 1891 and devoted the rest of her life to disseminating his work. She published his letters, organised exhibitions in the Netherlands and throughout the world, and made strategic sales to private individuals and influential dealers. Her efforts were crucial to the reputation of van Gogh’s art, but she also led an interesting life in other respects. Not only was she friends with eminent writers and artists, she was active within the Social Democratic Workers’ Party and closely involved in emerging women’s movements. Using rich source material, including unseen diaries, documents and letters, Hans Luijten charts the multi-faceted life of this driven woman who made a bold impact in a male-dominated world at the turn of the 20th century. His lovingly written biography also sheds new light on the complex history of public appreciation for Vincent van Gogh."
Keywords: Gogh-Bonger, Johanna Gesina van -- 1862-1925; Gogh, Vincent van -- 1853-1890; Biografie